Bromeliads at a Glance - Sydney Park Brown (EDIS)
ENH-1071, a 2-page illustrated fact sheet by Sydney Park Brown, provides basic information on these fascinating easy-to-grow, low-maintenance epiphytic plants that can be enjoyed indoors, outdoors in containers, or in the southern Florida landscapes, including blooming and propagation and pests. Includes references. Published by the UF Department of Environmental Horticulture, July 2007.